KONSELING TRAUMA PASCA BENCANA - Herman Nirwana (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2012)
As a country with thousands of islands, geographically Indonesia is very potential to natural disasters which cause great lost, environmental damage and psychological effects. Besides, violence, such robbery, rapes, and bombing frequently took place in Indonesia. It is estimated that 1.50 % of population suffered from Post Traumatic Stress Disorder (PSTD) due to the violence. Studies show in America that 15 up to 43 % of females and 14 up to 43 % of males experience trauma in their lives. Great numbers of individuals suffer from deep misery, uncertainty and desperation after natural disaster or violence and in turn leave them in stress, depression and trauma. One of services recommended to help those people go through with psychological problems is counseling, particularly relaxation and desensitization techniques.Kata kunci: trauma, konseling trauma